Pemberdayaan Pekerja Informal Untuk Kepersetaan Mandiri Dalam Asuransi Kesehatan - Nur Indah Nasution; Nadya Fitriyani; Indah Kumala Dewi (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Informal workers are a group that contributes significantly to the Indonesian economy, but still have a low level of independent participation in the national health insurance program. This low participation is caused by minimal insurance literacy, income instability, and a lack of awareness of the importance of health protection. This activity aims to empower informal workers to have the ability and willingness to become independent participants in health insurance. The method used is a community-based participatory approach through three main stages: education on the benefits of health insurance, microfinance management training for regular premium payments, and assistance with independent registration for participation. The activity results showed a significant increase in participants' knowledge and understanding of the benefits of health insurance. In addition, there was an increase in the number of informal workers registering as independent participants and demonstrating a commitment to sustainable premium payments. This program demonstrates that community empowerment can be an effective strategy to expand Universal Health Coverage (UHC) and improve the welfare of informal workers through sustainable health protection.